Agronomic and bread-making characteristics of durum wheat genotypes deriving from interspecific hybridisation with bread wheat - Palumbo M.; Spina A.; Boggini G. (Durum wheat improvement in the Mediterranean region: New challenges, 2000)
Modern durum wheat cultivars have been selected for pasta-making aptitude and usually present very strong and slightly extensible gluten, traits not suitable for bread-making utilisation. For this reason a breeding program was started with the aim of improving the bread-making quality of durum wheat. This research showed that the right relation between tenacity and elasticity of gluten greatly depends on some protein compositions rarely present in durum wheat cultivars, but frequent in lines or varieties obtained from interspecific hybridisation with Triticum aestivum. From this type of germplasm, 17 breeding lines were selected for agronomic traits and bread-making aptitude. The best agronomic and qualitative results were nevertheless found in the lines characterised by the glutenin subunits HMW Glu-A1 Null and Glu-B1 7 plus 8.
Seminar on Durum Wheat Improvement in the Mediterranean Region: New Challenges, 2000/04/12-14, Zaragoza (Spain)